Do institutions affect the wage structure? Right-to-work laws, unionization, and the minimum wage - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1999)
Union strength is capable of boosting wages for workers at the low end of the income scale. Even when differences in education and industry type are accounted for, workers in right-to-work states have a greater probability of earning close to the minimum wage than workers in states with relatively high union density. The decline of unionization requires that other labor market institutions, mainly the minimum wage, be used to improve the distribution of income in order to combat the continuing growth of inequality in the United States.
Keywords: 330